2013
DOI: 10.1038/nn.3576
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Purkinje cell activity drives motor learning

Abstract: The climbing fiber input to the cerebellar cortex is thought to provide instructive signals that drive the induction of motor skill learning. We found that optogenetic activation of Purkinje cells, the sole output neurons of the cerebellar cortex, can also drive motor learning in mice. This dual control over the induction of learning by climbing fibers and Purkinje cells can expand the learning capacity of motor circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 32 publications
11
130
1
Order By: Relevance
“…Together these results indicate a prominent role of the cerebellum in the after effects of motor training. The central role of the cerebellum and cortico-cerebellar loops in motor learning are consistent with existent literature (Raymond et al, 1996;Inoue et al, 2000;Della-Maggiore et al, 2009;Nguyen-Vu et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Together these results indicate a prominent role of the cerebellum in the after effects of motor training. The central role of the cerebellum and cortico-cerebellar loops in motor learning are consistent with existent literature (Raymond et al, 1996;Inoue et al, 2000;Della-Maggiore et al, 2009;Nguyen-Vu et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, stimulating simple spike activity of Purkinje cells either pharmacologically or optogenetically leads to an increase in the excitatory phase of the modulation amplitude of the simple spikes as well as an increase in the gain of compensatory eye movements (van der Steen and Tan 1997;De Zeeuw et al 2004;Nguyen-Vu et al 2013). Thus, in line with the data obtained by Wang and colleagues (2011) , which in turn innervate the oculomotor neurons (OMs) driving the eyes to the opposite side.…”
Section: Motor Learning In a Zebrin-positive Module: Adaptation Of Thsupporting
confidence: 68%
“…The CAG promoter as well as other ubiquitous promoters, such as cytomegalovirus or elongation factor-1α promoter, have been used for AAV-mediated transduction of cerebellar Purkinje cells (Broekman et al, 2006;Kaemmerer et al, 2000;Kaneko et al, 2011;Najafi et al, 2014;Nguyen-Vu et al, 2013;Xia et al, 2004). Consistently, we also confirmed that AAV1 with the CAG promoter (AAV1-CAG) successfully drove GFP expression in Purkinje cells of adult mice, which were visualized by staining with a calbindin antibody ( Fig.…”
Section: Broad Expression Patterns Of Transgenes Driven By the Cag Orsupporting
confidence: 80%
“…Viral vectormediated gene delivery in Purkinje cells has been performed in various research on neurodegenerative disorders as well as Purkinje cell development or function (Alisky et al, 2000;Broekman et al, 2006;Gibson et al, 2014;Kaemmerer et al, 2000;Kaneko et al, 2011;Najafi et al, 2014;Nguyen-Vu et al, 2013;Takayama et al, 2008;Torashima et al, 2006;Tsubota et al, 2011;Xia et al, 2004). Several serotypes of AAV were also tested, and expression of the transgene in Purkinje cells was observed using AAV serotype 1 (AAV1), 2, 5, or 8 (Hirai, 2008).…”
mentioning
confidence: 99%